Correction: Mallphanov et al. Novel Approach to Increasing the Amplitude of the Mechanical Oscillations of Self-Oscillating Gels: Introduction of Catalysts Both as Pendant Groups and as Crosslinkers. Gels 2024, 10, 727 - Ilya L. Mallphanov; Michail Y. Eroshik; Dmitry A. Safonov; Alexander V. Sychev; Vyacheslav E. Bulakov; Anastasia I. Lavrova (Gels)
In the original publication [...]